2021
DOI: 10.2196/30004
|View full text |Cite
|
Sign up to set email alerts
|

Using Venn Diagrams to Evaluate Digital Contact Tracing: Panel Survey Analysis

Abstract: Background Mitigation of the spread of infection relies on targeted approaches aimed at preventing nonhousehold interactions. Contact tracing in the form of digital proximity tracing apps has been widely adopted in multiple countries due to its perceived added benefits of tracing speed and breadth in comparison to traditional manual contact tracing. Assessments of user responses to exposure notifications through a guided approach can provide insights into the effect of digital proximity tracing app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
6
6
0
Order By: Relevance
“…Conversely, some selection may have also occurred, and participants included in the study may reflect populations with higher health literacy, which may also be more likely to comply with the recommended actions and undertake preventive actions after being notified by the DPT app. Nevertheless, our results are broadly consistent with a population-based assessment of actions taken by SwissCovid app users receiving an EN in which 76% of app users took at least 1 preventive action after EN [22].…”
Section: Limitationssupporting
confidence: 88%
See 2 more Smart Citations
“…Conversely, some selection may have also occurred, and participants included in the study may reflect populations with higher health literacy, which may also be more likely to comply with the recommended actions and undertake preventive actions after being notified by the DPT app. Nevertheless, our results are broadly consistent with a population-based assessment of actions taken by SwissCovid app users receiving an EN in which 76% of app users took at least 1 preventive action after EN [22].…”
Section: Limitationssupporting
confidence: 88%
“…On a positive note, the majority (n=14, 77.8%) of those receiving an EN before MCT undertook recommended measures, such as seeking SARS-CoV-2 testing (n=12, 66.7%) or calling the SwissCovid Infoline (n=7, 38.9%). Similarly, another Swiss study also found that 76% of EN-notified contacts undertook a recommended action [22]. These findings stand in contrast to an experimental study from Spain, which found that only 10% of the notified contacts acted upon EN receipt by calling a designated infoline [29].…”
Section: Principal Findingsmentioning
confidence: 79%
See 1 more Smart Citation
“…This was not observed in our study, where we found that relatively few app users who received exposure notifications ignored the exposure warning. Most of these app users undertook at least 1 recommended mitigative step in response to the notification, such as calling the infoline or completing the web form, which is in line with other studies from Switzerland [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 66%
“…For example, Salathé et al found that only 2 out of 3 upload authorization codes issued to SARS-Cov-2-infected cases were eventually uploaded to notify exposed contacts [20]. Furthermore, individual-level data from an online panel comprising approximately 2000 individuals from Switzerland suggest that only 3 of 4 exposed contacts undertook the recommended actions after receiving an EN [22]. Such findings are concerning since DPT effectiveness is built on the premise that users, i.e., cases after receiving the upload authorization code or contacts after receiving the EN, will undertake the necessary actions to prevent further transmission.…”
Section: Introductionmentioning
confidence: 99%